Research for Practice: The DevOps Phenomenon. - WIEDEMANN, ANNA; FORSGREN, NICOLE; WIESCHE, MANUEL; GEWALD, HEIKO; KRCMAR, HELMUT (Communications of the ACM, 2019)
The article discusses the DevOps method of software development in relation to executive leadership. Topics include the relation of organizational change to DevOps methodology, the relation of DevOps to project management, and the relation of research on DevOps to practices. The importance of organization culture is noted.